Management Strategies for Upgrading MSMEs in Facing Economic Uncertainty in Indonesia - Sabil, Sabil; Rosento, Rosento; Lahat, Mohammad Amas; Marthanti, Amas Sari; Suratriadi, Panji; Hi Lawu, Suparman (Dinasti Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting Indonesia's economic stability and growth, yet this sector faces serious challenges due to increasingly complex global and domestic economic uncertainties. In this context, understanding effective management strategies is crucial for MSMEs seeking to upgrade—that is, to transform into more structured, competitive business entities. This study aims to identify and synthesize the management strategies employed by MSMEs in responding to uncertain economic dynamics. Using a systematic literature review approach, this research analyzes 25 relevant open-access scholarly articles published over the past five years, thematically organized based on Porter's generic strategy framework, business resilience theory, and the MSME growth-stage model. The findings reveal that the primary strategies adopted by MSMEs include product differentiation, business process digitalization, and cross-sector collaboration through training, business incubation, and community partnerships. These approaches significantly contribute to enhancing the adaptive capacity and competitiveness of MSMEs amid economic pressures. This article offers conceptual contributions by integrating strategic management theory with the local MSME context in Indonesia, while also providing practical recommendations for policymakers and business practitioners to strengthen systemic and sustainable MSME development models moving forward.